A Postcolonial Study of Marxism as a Speculative Other in Tariq Rehman’s Short Stories Mai Baap and The Zoo - Javaid, Sundus; Sumaira; Munir, Uzma (Pakistan Languages and Humanities Review, 2022)
Postcolonialism, in recent years, tends to subvert dominant ideological discourses in order to dismantle the Eurocentric epistemological constructions. In this context, Postcolonialism engages itself with Marxism as a metanarrative, a speculative Other. Postcolonialism, in order to contest Western hegemony, intersects with Postmodernism as unified ideological discourses with skepticism and hence, maintain notion of difference within the notion of emancipation. The study deals with Tariq Rahman’s engagement with deconstructing the political epistemology of Marxism as a speculative Other. Rahman, through his short stories, tends to emphasize upon the study of cultural essentialism to pinpoint its merger with Postcolonial studies to shatter the universalistic binary representations of Self/Other and hence, problematizes Postcolonial identity. The major concern of the study is to question the hegemonic construct of modernist Marxism. Thus, Rahman through his stories extends disbelief towards the globalizing and unifying dispositions of Marxism as a speculative culture of the colonizer cum neo-colonizer.